Analisis Pengaruh Variasi Jumlah Lintasan Terhadap Tingkat Kepadatan Campuran Asphalt Concrete Wearing Course (AC-WC) - Windy Agustin Putri; Siti Nurjanah Ahmad; Anafi Minmahddun (Jurusan Teknik Sipil, Universitas Halu Oleo, 2024)
In this research, we discuss how to determine the number of density path variations in compaction trials. The aim of this research is to find out the relationship between variations in the number of compaction passes in the field and the density of the Asphalt Concrete Wearing Course (AC-WC) mixture and determine the number of asphalt compaction passes based on the results of compacting trials in the field (trial compacting). The method used is the cause and effect relationship method. The cause and effect relationship that will be analyzed is how the number of compaction passes of the asphalt mixture relates to the density of the asphalt mixture. From the results of calculating field density in the variation 1 compaction experiment with a number of passes of 16, the density result was 96.71%. In the compaction experiment variation 2 with a number of passes of 18, the density result was 99.81%. Of the two variations, the Laston layer is variation 2 with 18 passes with a result of 99.81%, because variation 2 has the most ideal density value with the minimum requirements of the 2018 general specifications revision 2.